Substituents’ influence on the C–H interaction in the T-shaped benzene dimer - Mishra B.K.; Venkatnarayan R. (My University, 2025)
We have investigated the CH interaction in the T-shaped benzene dimer in the presence of various neutral and cationic substituents, using the CCSD(T)/CBS and B97D/aug-cc-pVTZ method. The results reveal that the strength of the CH interaction can be enhanced up to 3.57 kcal/mol for multiple fluorine substitutions. The interaction energy of the dimer can be further increased by choosing electron-withdrawing substitutions, such as nitro and cyano groups. Further, the CH interaction energy can be tuned from ~ 5 to ~ 10 kcal/mol by the choice of cationic substituents. The energy decomposition results reveal that, on an average, the dispersion energy is two times larger than the electrostatic energy. However, the total binding energy follows the trend observed in the electrostatic energy component. © 2018, Springer-Verlag GmbH Germany, part of Springer Nature.